Urunwakaf.com : Gaya Baru Pengelolaan Wakaf Uang Guna Pemberdayaan Ekonomi Masyarakat dan UMKM di Masa Pandemi Covid 19 - Nugroho Heri Pramono; Eldes Willy Filatrovi; Ananda Genta Tribuana (Universita Bangka Belitung, 2022)
Money waqf is one of the instruments of Islamic philanthropy that plays a role in empowering the economy for the benefit of society. However, not many people have received education about cash waqf and its management. Especially the people in Central Java Province. Based on the results of a survey conducted by the STIE Bank BPD Central Java community service team randomly by conducting interviews with the community and MSMEs, it was found that there were still few people who understood waqf and its derivative types such as cash waqf. Even if they know, it is only limited to waqf for mosques, schools and graveyards. Therefore, STIE Bank BPD Central Java's internal community service was created with the aim of providing alternative solutions for community and MSME empowerment in Central Java province during the COVID-19 pandemic, by creating fintech for the management of cash waqf for community empowerment and MSMEs. The cash waqf management model is carried out by creating a crowdfunding platform-based organization with a waqf contract. The collected cash waqf funds are used for community empowerment andMSMEs in Central Java who have been affected by the COVID19 pandemic with a profit-sharing agreement. Profit sharing from the community and MSMEs is used for fintech operations, crowdfunding of waqf and equitable distribution of income to people in need. Meanwhile, the waqf funds returned from the profit-sharing contract are used for repeated empowerment of the community and MSMEs in rotation